Screening ANLN and ASPM as bladder urothelial carcinoma-related biomarkers based on weighted gene co-expression network analysis - Yang, Tenghao; Chi, Zepai; Liu, Guoyuan; Hong, Xuwei; Cao, Sizhe; Cheng, Kequan; Zhang, Yonghai (Frontiers in Genetics, 2023)
Bladder cancer (BLCA) is one of the most common malignancies in the urinary system with a poor prognosis and high treatment costs. Identifying potential prognostic biomarkers is significant for exploring new therapeutic and predictive targets of BLCA. In this study, we screened differentially expressed genes using the GSE37815 dataset. We then performed a weighted gene co-expression network analysis (WGCNA) to identify the genes correlated with the histologic grade and T stage of BLCA using the GSE32548 dataset. Subsequently, Kaplan Meier survival analysis and Cox regression showed that Anillin (ANLN) and Abnormal spindle-like microcephaly-associated gene (ASPM) were prognostic biomarkers for BLCA. High expression of ANLN and ASPM was associated with poor overall survival. Moreover, we detected the expression of ANLN and ASPM in 35 paired samples, including BLCA and paracancerous tissue, from the Shantou Central Hospital by qRT-polymerase chain reaction. The results revealed that ANLN and ASPM genes were upregulated in BLCA, and there was a correlation between the expression of ANLN and ASPM in cancer tissues and paracancerous tissue. Additionally, the increasing multiples in the ANLN gene was obvious in high-grade BLCA. In summary, this preliminary exploration indicated a correlation between ANLN and ASPM expression. These two genes, serving as the risk factors for BLCA progression, might be promising targets to improve the occurrence and progression of BLCA.